Energy policy of the Republic of Turkey: expansion in the Eastern Mediterranean - B. D. Nuriev; S. V. Pospelov (Вестник университета)
The article analyzes the modern energy policy of the Republic of Turkey in the Eastern Mediterranean, conducted in line with the center-right ideology of regional dominance. The authors state that the main reason for the emergence of interstate contradictions in the region is the formation of national states in the first half of the last century, whose administrative borders were drawn up and recognized without taking into account ethnic characteristics and centuries-old economic traditions. Another important reason is the desire of official Ankara and the Turkish big business that has taken shape over the past two decades to strengthen its influence in neighboring countries and territories. Modern Turkey, deprived of its own islands in the waters of the eastern Mediterranean and Aegean Seas, insists on revising a number of provisions of international maritime law, which increases the level of tension in the region as a whole, and in Turkish-European relations in particular. The article also emphasizes that the unresolved important interstate problems in the Eastern Mediterranean and Turkey’s active policy in this region opens up new opportunities for the Russian oil and gas business, which require their own balanced expert assessment.